Retrospective study on the incidence and outcome of proven and probable invasive fungal infections in high-risk pediatric onco-hematological patients. - Cesaro, Simone; Tridello, Gloria; Castagnola, Elio; Calore, Elisabetta; Carraro, Francesca; Mariotti, Ilaria; Colombini, Antonella; Perruccio, Katia; Decembrino, Nunzia; Russo, Giovanna; Maximova, Natalia; Baretta, Valentina; et al. (Eur J Haematol, 2017)
BACKGROUND: Invasive fungal infection (IFI) is a cause of morbidity, mortality and increased health costs in children undergoing chemotherapy or hematopoietic stem cell transplant (HSCT). METHODS: Multicenter, retrospective study to assess the incidence, outcome of proven and probable IFI (PP-IFI) in children treated for acute leukemia, non-Hodgkin lymphoma or who underwent HSCT from 2006 to 2012. RESULTS: Over the 7-year period, 127 PP-IFI were diagnosed in 123 patients, median age of 9.7 years. The 1-year cumulative incidence was 2.5% (CI 1.8-3.7) after frontline chemotherapy, 9.4% (CI 5.8-15.0) after relapse, and 5.3% (CI 3.9-7.1) after HSCT. Severe neutropenia was present in 98 (77%) patients. Culture-proven agents were Candida spp., mostly non-albicans, 28, mold 23, whereas three proven IFI were identified by histopathology. Favorable response to treatment within 3 months from diagnosis was observed in 77 (89%). The overall ninety-day probability of survival was 68% (CI 59-76). CONCLUSIONS: About two-thirds of pediatric patients with PP-IFI survived, regardless of whether the infection occurred after frontline chemotherapy, reinduction chemotherapy for disease relapse, or after HSCT. Further prospective studies are needed to define the impact of antifungal prophylaxis and early combination therapy on short-term overall survival.
Keywords: Adolescent; Antifungal Agents; Antineoplastic Combined Chemotherapy Protocols; Child; Child, Preschool; Drug Therapy, Combination; Female; Hematologic Neoplasms; Hematopoietic Stem Cell Transplantation; Humans; Incidence; Male; Mycoses; Patient Outcome Assessment; Retrospective Studies; Survival Analysis; Treatment Outcome